You and your profile : identity after authenticity - Moeller, Hans-Georg; D'Ambrosio, Paul J. (Columbia University Press, 2021)
More and more, we present ourselves and encounter others through profiles. A profile shows us not as we are seen directly but how we are perceived by a broader public. As we observe how others observe us, we calibrate our self-presentation accordingly. Profile-based identity is evident everywhere from pop culture to politics, marketing to morality. But all too often critics simply denounce this alleged superficiality in defense of some supposedly pure ideal of authentic or sincere expression.This book argues that the profile marks an epochal shift in our concept of identity and demonstrates why that matters. You and Your Profile blends social theory, philosophy, and cultural critique to unfold an exploration of the way we have come to experience the world. Instead of polemicizing against the profile, Hans-Georg Moeller and Paul J. D’Ambrosio outline how it works, how we readily apply it in our daily lives, and how it shapes our values—personally, economically, and ethically. They develop a practical vocabulary of life in the digital age. Informed by the Daoist tradition, they suggest strategies for handling the pressure of social media by distancing oneself from one’s public face. A deft and wide-ranging consideration of our era’s identity crisis, this book provides vital clues on how to stay sane in a time of proliferating profiles.
Keywords: Identity (Psychology)